Age-Related Macular Degeneration Prevalence and its Risk Factors in Iran: A Systematic Review and Meta-Analysis Study - Parsa Panahi; Ali Kabir; Khalil Ghasemi Falavarjani (Journal of Current Ophthalmology)
Purpose: To estimate the prevalence of age-related macular degeneration (AMD) and determine its risk factors in Iran. Methods: A comprehensive electronic search was conducted in PubMed, Scopus, Web of Science, and Google Scholar, with no restrictions on time or language of publication. Eleven studies meeting the eligibility criteria were included. Six studies with a total sample size of 9930 were included in the meta-analysis to calculate the overall prevalence of AMD in Iran. Meta-analysis was performed using Stata/MP version 15.0. Risk of bias assessment was carried out based on the Newcastle–Ottawa Scale. Results: All participants in the studies were over 40 years old. The pooled prevalence of AMD was estimated to be 9.9% (95% confidence interval [CI]: 6.3%–13.5%). After accounting for publication bias, this estimated decreased to 6.4% (95% CI: 4%–10.2%). Smoking (odds ratio [OR]: 1.781; 95% CI: 1.152–2.756), hypertension (HTN) (OR: 1.512; 95% CI: 1.119–2.044), diabetes mellitus (DM) (OR: 1.545; 95% CI: 1.088–2.194), and hyperlipidemia (OR: 1.512; 95% CI: 1.055–2.165) were identified as AMD risk factors. Conclusion: Based on the results of the present review, the prevalence of AMD in the Iranian population over 40 years of age is estimated to be 6.4%, and having a history of smoking, HTN, DM, and hyperlipidemia are identified as risk factors of AMD in Iran. Further original studies are needed to draw more accurate conclusions.